The compound specific antibacterial activities of major urolithins and their methyl ethers - Gülcan, Hayrettin Ozan; Ilktaç, Mehmet; Noshadi, Bahareh; Shukur, Karar Tawfeeq; Gazi, Mustafa (Turkish Chemical Society, 2021)
The investigation of biological activities of natural products, particularly considering the secondary metabolites, continuously receives attention. Urolithins, the bioavailable metabolites of ellagitannins, were shown to possess enzyme inhibitor, antioxidant, and anti-inflammatory compounds in scientific studies conducted in the last two decades. Regarding the limited number of studies related to their antimicrobial activity, this study aimed to synthesize major urolithins (Urolithin A and B) concomitant to their methyl ether derivatives and screen their antibacterial activity against some Gram positive and Gram negative bacteria. In parallel to the antibacterial activity, the synergistic and antagonist properties of the compounds were also analyzed in the presence of reference beta-lactam antibiotics. The results displayed the improvable characteristics of urolithin scaffold to be employed in antibiotic drug design studies. In addition, the antagonist effect of some compounds on the antibacterial action of standard molecules also pointed out the compound specific activities of the title molecules. © 2021, Turkish Chemical Society. All rights reserved.
Keywords: Antagonism; Antibacterial activity; Synergism; Synthesis; Urolithin